Influencia de la inteligencia Kinestésica en el desarrollo de las habilidades motrices básicas, en estudiantes del cuarto grado A, de la Unidad Educativa Lauro Damerval Ayora, Loja, 2023 - Herrera Velez, Anthony Reinaldo (2024)
This Curricular Integration Work was developed with the objective of determining how kinesthetic intelligence influences the development of basic motor skills in students of the fourth grade parallel “A”, of the Lauro Damerval Ayora Educational Unit, in the Loja city during the period 2023. The study was conducted based on the mixed approach, being of correlational type and quasi-experimental design. Diagnostic instruments such as an observation sheet and a test were applied to a sample of 20 students. According to the results obtained once the diagnostic instruments were applied, it is evident that the mean of motor awareness presented by the participants was 119.6, which means that the motor consciousness of the participants was good. These results are not bad taking into consideration the rest of indicators, in spite of this, there is room for improvement in these aspects. Based on these results, a pedagogical proposal based on Kinesthetic Intelligence was designed and applied, which was structured in 12 class sessions with activities related to the development of basic motor skills in physical education classes. Afterward, control instruments were applied where improvement was evidenced in the aforementioned aspects, achieving an average in the motor conscious of 141.17, placing it in the very good indicator. It is concluded that before the application of the proposal there were certain difficulties in the execution of balance and coordination exercises, due to the lack of development of basic motor skills. On the other hand, after the application of the proposal it was improved in these aspects, demonstrating thus the effectiveness of the use of kinesthetic intelligence for the development of basic motor skills. Keywords: Intelligence, Kinesthetic Intelligence, Methodology, Basic motor skills, Coordination and Balance